2015
DOI: 10.1097/inf.0000000000000599
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Retropharyngeal Abscess in Children

Abstract: A retrospective review of 33 patients comparing community-associated methicillin-resistant Staphylococcus aureus retropharyngeal abscess (RPA) with community-associated methicillin-susceptible S. aureus RPA from 2002-2013 at Texas Children's Hospital revealed most cases of S. aureus RPA have been due to community-associated methicillin-resistant S. aureus, which appears to be associated with a more complicated clinical course than RPA caused by community-associated methicillin-susceptible S. aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
0
11
0
3
Order By: Relevance
“…Los abscesos retro y parafaríngeos son complicaciones infecciosas del espacio cervical profundo poco frecuentes actualmente y que suelen acontecer en niños menores de 5 años más que en adultos. Sin embargo, son muy infrecuentes en lactantes menores de 1 año [1]. La mitad de estos refieren antecedentes de infección de vías altas previa al episodio que provoca un cuadro de linfadenitis supurativa cervical y un menor porcentaje es atribuido a haber sufrido algún traumatismo en el espacio retrofaríngeo [2].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Los abscesos retro y parafaríngeos son complicaciones infecciosas del espacio cervical profundo poco frecuentes actualmente y que suelen acontecer en niños menores de 5 años más que en adultos. Sin embargo, son muy infrecuentes en lactantes menores de 1 año [1]. La mitad de estos refieren antecedentes de infección de vías altas previa al episodio que provoca un cuadro de linfadenitis supurativa cervical y un menor porcentaje es atribuido a haber sufrido algún traumatismo en el espacio retrofaríngeo [2].…”
Section: Discussionunclassified
“…Además, hay signos y síntomas que deben alertar por corresponder a la obstrucción de vía aérea o digestiva como disfagia, odinofagia, tortícolis, trismus, cambios en la voz, distrés respiratorio, etc. [1,2,7]. La exploración física del paciente con probable absceso cervical profundo debe ser realizada por especialistas experimentados en manejo de la vía aérea urgente pues la ruptura puede acontecer durante la misma.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Several studies have suggested that younger children have increased risk for complications, such as mediastinitis and also for infection due to MRSA. 37,38 The aggregate data suggest that children under the age of 2 years should be monitored more closely for complications, for presence for MRSA infection, and for the need for surgical intervention.…”
Section: Judicious Use Of Computed Tomography In Pediatricsmentioning
confidence: 99%
“…It is also important to obtain an exposure history such as animal contacts, specifically with kittens or cats, close contact with anyone at risk for tuberculosis, or with a recent history of methicillin-resistant Staphylococcus aureus (MRSA). 6 On physical examination, careful inspection of the oral cavity including floor of the mouth, teeth, gums, oropharynx should be performed to determine a possible source of lymphadenitis and for a potential airway compromise. The neck should be inspected for asymmetries and if identified the neck mass should be measured and the location (midline or lateral) documented.…”
Section: Clinical Manifestations Of Dnismentioning
confidence: 99%